R&D Personnel Career Routes: An Exploratory Study - Barbara Bigliardi; Alberto Ivo Dormio (Journal of Technology Management & Innovation, 2009)
This study, aiming at investigate the alternative modes of career development for personnel belonging to R&D staff, addresses the extent to which career anchors are applicable to R&D staff and to examine the relationship among career anchors, gender and age, with the final purpose to add elements of discussion to the long-lasting debate about this matter. With this purpose in mind, we developed a questionnaire survey among 309 R&D personnel employed at firms belonging to the food machinery industry in a Northern Italy district. The results obtained from the statistical analysis indicate that the R&D personnel’s career orientations is a predictor of their career routes preferences, confirming three possible career routes in R&D labs that were highlighted in previous studies.